Analisis Kualitas Pelayanan Pemberian Santunan Bagi Korban Kecelakaan Lalu Lintas Jalan Raya Pada Kantor PT. Jasa Raharja (Persero) Gunungsitoli - Jonatan, Septian; Kadir, Abdul; Siregar, Nina Siti Salmaniah (Universitas Medan Area, 2020)
This study aims to analyze the Service Quality of Providing Compensation for Victims of Road Traffic Accidents at the Office of PT. Jasa Raharja (Persero) Gunungsitoli. This type of research is descriptive with a qualitative approach, with research informants as Head of Raharja Gunungsitoli Services, Raharja Gunungsitoli Public Relations, Police Resort Public Relations of Nias Resort and the community / victims / heirs of victims of traffic accidents. In this research, a data analysis technique is used, which is a qualitative descriptive method. The results of this study indicate that the quality of traffic accident insurance services at PT. Jasa Raharja Persero Gunungsitoli, which is seen from 6 (dimensions), namely Transparency, Accountability, Conditional, Participation, Equal Rights, and Balance of Rights and Obligations, in general has been running well in accordance with existing provisions and service standards. Of the six dimensions, there is only one dimension that is still considered to be unfavorable, namely equality of rights and obligations. This can be seen from the services provided by PT. Jasa Raharja (Persero) takes precedence over major accidents compared to those affected by individual accidents.